Enhancing Community Participation in Village Planning: Cahaya Negeri Case Study - Hardayani, Yorry; Yogopriyatno, Jatmiko (JURNAL ABDIMAS SERAWAI, 2025)
This community service activity aimed to strengthen participatory planning processes in Cahaya Negeri Village, Seluma Regency. Lack of community participation in development planning has resulted in programs that are less responsive to local needs and aspirations. The service implemented a three-pronged approach: raising community awareness about the importance of participation, building capacity in communication and decision-making skills, and facilitating participatory planning processes through Focus Group Discussions. The implementation used Participatory Rural Appraisal (PRA) and Community Development models. Results showed increased community awareness regarding their role in village development planning, improved communication skills among participants, and more active engagement in development planning forums. The participatory approach fostered greater community ownership over development programs and improved relations between village administrators and residents. This initiative demonstrates how a well-designed participatory planning facilitation can enhance local democracy, strengthen village governance, and contribute to more sustainable rural development.